Exploring Gingival Overgrowth Due to Epileptic Medication: A Case Report - Srimayee Chaudhuri; Rahul Sarkar; Kaynat Parween (Oral Sphere Journal of Dental and Health Sciences, 2025)
Background: Gingival tissue hyperplasia is a condition that affects oral hygiene, aesthetics, and quality of life. Commonly associated with the use of some antiepileptic drugs (AEDs) like phenytoin and sodium valproate, this condition has become a normal occurrence in patients who take ATPs for seizure management because of the side effects that come along with the adverse tissues growth. Case Presentation: A 21-year-old female who had been taking sodium valproate to control her seizures developed severe gingival overgrowth. The clinical exam showed significant overgrowth in the anterior gingival area and with the overgrowth came inflammation along with symptoms of bleeding and bad breath (halitosis). The initial intervention of the problem (overgrowth) was some steps to improve oral hygiene with the use of some chlorhexidine mouthwash along with a short course of some antibiotics. But because of the severity of the overgrowth, surgical intervention to excise some of the overgrown tissue was performed. The tissue that was excised had a histopathological exam that confirmed the diagnosis along with giving some information for the changes in the tissue (cellular) to help understand the condition. Conclusion: This case highlights the importance of a multidisciplinary approach in managing DIGO, which includes regular dental monitoring, improved oral hygiene practices, and surgical interventions when necessary.